A Case of Persistent Hypoglycemia: Emphasizing the Role of Kidneys - Praveen Govindaraju; Mohammed Fahad Khan; Rohan Augustine; Hebri Sudarshan Ballal (Journal of Diabetology)
Abstract Hypoglycemia is an important cause of morbidity and mortality in patients with diabetes mellitus. However, hypoglycemia in patients without diabetes warrants extensive clinical and biochemical evaluations. Traditionally, it occurs either in patients with underlying illness or is seemingly healthy. In patients with underlying comorbidities, hypoglycemia is usually straightforward and may be multifactorial in etiology. A particularly vulnerable population is patients with chronic kidney disease (CKD). We hereby describe a case of persistent hypoglycemia in a 73-year-old nondiabetic CKD presenting as a diagnostic enigma and the possible mechanisms behind it.